Studi Deskriptif Kejenuhan Belajar dalam Pelaksanaan Program Tahfiz di Pondok Pesantren - Ulfa Danni Rosada; Atina Shofiana (Journal of Society Counseling, 2026)
This study aims to describe the level of learning saturation of students in the implementation of the Tahfiz Al-Qur'an program at the Az-Zayadiy Sanggrahan Islamic Boarding School. The research uses a quantitative approach with descriptive methods and survey techniques. The population comprises 268 students, and a sample of 160 students is selected using purposive sampling. Data collection was carried out using a scale questionnaire compiled based on three aspects of learning saturation according to Maslach: emotional fatigue, depersonalization, and decreased personal achievement. The data was analyzed using descriptive statistics to find out the general picture of the level of student learning saturation. The results of the study showed that the learning boredom rate of students was in the medium category of 72.74%. Most of the students (67.5%) are in the medium category, while the rest are in the low (16.9%) and high (15.6%) categories. Based on aspect analysis, emotional fatigue becomes a high dimension, followed by a decrease in personal achievement, while depersonalization is at a lower level. The findings of this study confirm the importance of the role of tahfiz supervisors in helping students manage learning boredom through mentoring that not only focuses on memorization achievement, but also pays attention to psychological and spiritual aspects. An approach that integrates emotional support, a variety of learning methods, and the strengthening of spiritual values is expected to help students maintain a balance between learning demands and emotional conditions. The results of this research are expected to be the basis for developing a mentoring strategy that is more responsive to the needs of students in the tahfiz program.